La afectividad de los padres para fortalecer la autoestima de las niñas y niños de 3 a 5 años de edad del nivel inicial I y II de la unidad educativa intercultural bilingüe Mushuk Rimak de la parroquia San Lucas del cantón y provincia de Loja. Periodo 2014-2015 - Guaillas Quihzpe, Curi Sisa (2016)
This research includes a study on the affection of parents to strengthen the self-esteem of girls and children from 3 to 5 years of age of the initial level I and II the unit Education Intercultural bilingual Mushuk Rimak of the parish San Lucas of the Canton of Loja province. 2014-2015 period. For which arose as a general objective, which is the following: contribute to strengthen the self-esteem of girls and boys through the affection of parents. The methodology consists of the following methods: method, scientific, analytical, synthetic, hermeneutic and the statistician. The observation technique was used for the collection of the information and the instrument was a valuation of child self-esteem and a survey Guide for parents. The population was of 11 children and 11 parents. Through assessment and Survey Guide, demonstrate that 64% which corresponds to 7 children presented a proper self-esteem and 36% which corresponds to 4 children had conflicts in the development of their self-esteem; While 73% representing 8 parents retained a proper self-esteem, and 27% representing 3 fathers had self-esteem problems. After doing a workshop for a month to parents; We proceeded to again apply the rating guide to each of the children who had the problem, resulting in that 4 children was achieved that 3 children amounting to 75%, I get to have adequate self-esteem. We concluded that the affection of parents is important sum for the development of the self-esteem of children.